Influence of social upbringing on the activity pattern of captive lion Panthera leo cubs: Benefits of behavior enrichment - Sibonokuhle NCUBE, Hilton Garikai Taambuka NDAGURWA (Current Zoology, 2010)
The influence of social upbringing on the activity pattern of lion Panthera leo cubs was investigated at three sites. In this study, stimulus objects such as sticks, grass, fresh dung (elephant Loxondota africana, zebra Equus quagga, impala Aepyceros melampus, duiker Sylvicapra grimmia, kudu Tragelaphus strepsiceros, giraffe Giraffa camelopardalis and wildebeest Connochaetes taurinus) and cardboard boxes, were utilized in an enrichment program aimed at encouraging active behaviors of captive lion cubs at Antelope Park and Masuwe. Lion cubs at Chipangali were not behaviorally enriched. Activity patterns were recorded for 10 days at each site. We recorded moving, resting, playing, grooming, visual exploration and display of hunting instincts. We found that behavioral enrichment enhanced the active behaviors of captive lion cubs. Orphan-raised cubs spent more time moving, playing and displaying hunting instincts than mother-raised cubs, but the time spent grooming was similar across areas and suggests that grooming is not influenced by enrichment. Mother-raised cubs spent more time engaged in visual exploration than orphan-raised cubs and this could be a behavior acquired from mothers or a result of confidence to explore because of their presence. Activity patterns were different among time treatments across our three study sites. Based on these findings, we suggest that lion cubs raised in captivity could benefit from behavioral enrichment to encourage active behaviors essential for eventual reintroduction into the wild [Current Zoology 56 (4): 389–394, 2010].